Exploring semiotic metaphorical representation in John Donne’s “The Flea”: A Systemic Functional Linguistic Analysis - Makinde, Peter (Journal of English Language Teaching and English Linguistics, 2025)
This study explores a semiotic metaphorical representation of John Donne’s “The Flea”. Through a detailed examination and interpretation of the linguistic features and structures used in the poem, the study uncovers the underlying meaning and significance behind the metaphors used by Donne. It examines the use of symbols, language choice, allusion, lexical items, and allegories and how they are recontextualised as semiotic resources to create a multi-layered representation. Data for the study is drawn from John Donne’s poetic text, “The Flea”. Using Halliday and Matthiessen’s Systemic Functional Linguistics (SFL) framework, the study aims to deconstruct how Donne employs language to convey complex meaning through his metaphysical masterpiece. AntConc software is also used to determine the frequency of the poem’s most frequently used lexical items. Findings from this study provide a deeper understanding of the poet’s intention and contribute to the existing body of literature on semiotic representation, metaphorical exploration, and lexical density that help to depict the overall beauty of the structure of the poem. The study also provides insights into the complex relationship between linguistics and literary analysis and reveals how such a symbiotic relationship enhances the teaching and learning of stylistics from an SFL perspective.